Bioactive flavones isolated from Tunisian Artemisia campestris L. Leaves - Metoui, Rafika; Bouajila, Jalloul; Znati, Mansour; Cazaux, Sylvie; Neffati, Mohamed; Akrout, Ahmed (Cellular and Molecular Biology, 2017)
Four flavones were isolated from dried leaves of Artemisia campestris L. 2’,4’,5,7-tetrahydroxy-5’,6-dimethoxyflavone, eupatilin and dimethoxycentaureidin were reported for the first time in this species whereas cirsiliol was previously identified but it was isolated for the first time. Their structures were elucidated by spectroscopic methods, including 1D and 2D NMR experiments and mass spectrometry analysis. In addition, all isolated flavones were evaluated for their antioxidant, anti-inflammatory, anti-superoxide dismutase, anti-xanthine oxidase and cytotoxic activities. The results showed that all isolated compounds exhibited potent anti-xanthine oxidase activity with IC50 ranging from 3.3 to 6.8 µM, which was higher than that of the control compound allopurinol (8.2 ± 0.6 µM). In addition, cirsiliol was found to be the most cytotoxic against OVCAR-3, IGROV-1and HCT-116 cell lines at 15µM, with inhibition percentage values of 53.7, 48.8 and 40.9%, respectively. All compounds also showed weak to moderate anti-inflammatory and anti-superoxide dismutase activities.